Barriers and facilitators to scaling up Healthy Choices, a motivational interviewing intervention for youth living with HIV - Karen MacDonell; Veronica Dinaj-Koci; Juline Koken; Sylvie Naar (BMC, 2022)
Abstract Background This study included Community Health Workers and their supervisors from HIV clinical care teams who participated in the Healthy Choices intervention program. Healthy Choices is a Motivational Interviewing-based intervention aimed at improving medication adherence and reducing alcohol use for adolescents and emerging adults ages 16-24 living with HIV. In this study, the intervention was "scaled up" for delivery by local HIV care providers in real-world clinic settings. Methods Providers (N = 21) completed semi-structured interviews (N = 29) about their experiences with intervention scale-up. Rigorous thematic analyses were conducted within discussions of barriers and facilitators of intervention implementation. Results Three dominant thematic areas emerged from the data: (1) perceptions of the Healthy Choices intervention, (2) engaging high risk YLH in in-person behavior interventions, and (3) perspectives on implementation of the intervention using local staff. Results offer insights into implementation of MI-based interventions for adolescents and emerging adults in clinic settings using local clinical staff instead of dedicated research staff. Conclusions Overall, scaled-up intervention programs for youth are challenged to maintain scientific rigor, provide rigorous training and supports, and offer an attractive and engaging program.